Scalable electric-field-assisted fabrication of vertically aligned carbon nanotube membranes with flow enhancement. (February 2020) - Castellano, Richard J.; Praino, Robert F.; Meshot, Eric R.; Chen, Chiatai; Fornasiero, Francesco; Shan, Jerry W.
Abstract: We report a solution-based approach for fabricating vertically aligned carbon-nanotube (VACNT) membranes, which improves on the unaligned nature of CNT mixed-matrix membranes. This approach addresses important challenges regarding scalability and incorporation of different types and sizes of nanotube as pores in a membrane. In a new, solvent-deposition approach, CNTs are dispersed and then aligned and concentrated via electro-deposition from an organic solvent, using a composite AC + DC electric field to form aligned CNT arrays. This enables VACNT number densities that are two orders-of-magnitude higher than possible from direct suspension of CNTs in the liquid oligomer. The solvent is then replaced by a UV-curable oligomer, which is selectively cured to form macroscopic membranes of highly controlled thickness. After plasma etching to open pores, the VACNT membranes are shown to be permeable, and to have pore sizes consistent with flow through internal channels of the CNTs. In a first for field-aligned, solution-fabricated VACNT membranes, the pores show substantial, 100–300 ×, gas-flow enhancement compared to theory, similar to membranes fabricated via less scalable methods ( i.e., by CVD growth of already aligned CNT forests). The solution-based, electric-field-assisted approach aligns nanotubes of different sizes and types grown by any means, and is scalable to the efficient fabrication of large-area VACNT membranes for a variety of important applications. Graphical abstract: Image 1 Highlights: First solution-fabricated, electric-field-aligned CNT membranes with demonstrated flow through CNT pores. Demonstrated flow enhancement (100–300 × over conventional theory) for the first time in electric-field-aligned CNT membranes. Developed rapid, non-destructive method for pore-size measurement using flowrate ratio of two gases.